Study on soil freezing characteristic curve during a freezing-thawing process - Bi, Jun; Wu, Zhijian; Lu, Yu; Wen, Haiyan; Zhang, Yingmin; Shen, Yunxia; Wei, Tingting; Wang, Guoxu (Frontiers in Earth Science, 2023)
Soil freezing characteristic curve (SFCC) defines the relationship between unfrozen water content and subzero temperature. The SFCC is widely applied to estimate the soil properties. The current study explored the effects of initial water content, dry density, soil type and desalination on the SFCC during a freezing-thawing process. It showed that the initial water content, soil type and desalination had great impacts on SFCC, while the dry density had an insignificant effect on SFCC. Hysteresis behavior was observed for all the soil samples. The hysteresis behavior was obvious in the temperature range of -5℃ < T < 0, but not obvious in the temperature range of T ≤ -10 ℃. A new equation containing freezing/thawing point was proposed to model the SFCC. The new model and 4 SFCC models were evaluated with measured data in this study. It showed that the new model performed best among these models. The new model accurately mimics the SFCC and is continuous near the freezing/thawing point and 0 ℃. It can be easily incorporated into numerical algorithms for coupled heat and mass transfer in cold regions.